Retrospective survey of bronchoalveolar lavage fluid cytology in Western Australian horses presented for evaluation of the respiratory tract: effect of season on relative cell percentages. Issue 5 (May 2015) - Secombe, CJ; Lester, GD; Robertson, ID; Cullimore, AM
<x xml:space="preserve">Abstract</x> Objective To characterise the cytological changes in equine bronchoalveolar lavage (BAL) samples over multiple years to determine if the prevalence of a relative mast cell response was influenced by season. Methods Medical records of 228 horses with clinical signs consistent with non‐infectious respiratory disease or poor performance where a BAL was performed were reviewed retrospectively. BAL fluid cytology and categorised clinical variables were analysed using a Chi‐square test to determine associations. Results The predominant signalment was a racing horse between 2 and 6 years of age, and poor athletic performance was the most common presenting complaint. Based on published criteria, 69.7% of horses had abnormal BAL cytology. The presence of nasal discharge was the only clinical finding that differed significantly between horses with abnormal and normal cytology. The most common cytological derangement was a mixed cell response (26.7%), the majority of which comprised elevated percentages of neutrophils and mast cells. A solely neutrophilic response or mast cell response occurred with equal frequency (18% and 18.95%, respectively), and an isolated eosinophilic response was noted in 6.1% of cases. Of the horses with cytology consistent with non‐infectious lower airway inflammation, 58.4% had increases in the relative percentage of mast cells. Cell profiles were significantly associated with season, with mastocytosis occurring more commonly in spring, whereas eosinophilic and neutrophilic responses were more common in summer. Conclusion In this study, a relative mast cell increase was the most common cytological profile in horses with lower airway inflammation and was associated with season.